อิทธิพลของการเจือ ไนโอเบียม อินเดียม และ อะลูมิเนียม ในไทเทเนียมไดออกไซด์เซรามิกต่อสมบัติทางไดอิเล็กทริก - ยุทธพิชัย ขำมณี (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
In this work, it is of interest to develop electrical properties of titanium dioxide dielectric ceramics by doping with niobium (Nb), indium (In), and aluminium (Al). Samples were synthesized by solid-state reaction method. Samples were sintered at 1,450 oC for 10 hours. Samples were divided into 3 group. The first group is 1, 5, and 7 mol% (In,Nb) co-doped TiO2. Dielectric permittivity of undoped is 400 when doping at 1, 5, and 7 mol% of (In,Nb), it increased to 600, 8,000 and 14,000, respectively. The second group is 5 mol% (In,Nb) co-doped TiO2, which indium concentration was adjusted to be deficient and excess. The ratios of Nb:In used in this doping condition are 0.50:0.47, 0.50:0.48, 0.50:0.49, 0.50:0.51, 0.50:0.52 and 0.50:0.53. Dielectric permittivity of indium-deficient conditions are 28,000, 22,000 and 30,000, respectively. It showed higher value than indium-excess conditions, which are 17,000, 12,000 and 13,000, respectively. The third group is 5 mol% (Nb,In,Al) co-doped TiO2, the ratios of Nb:In:Al dopants are 0.005:0.475:0.025, 0.005:0.450:0.050 and 0.005:0.425:0.075. It exhibited outstanding physical and electric properties. XRD results confirm that all sample formed a single phase. It exhibited average grain size of 25.94, 23.24 and 40.20 micrometer, respectively, and dielectric permittivity of 27,000, 25,000 and 43,000, respectively. Dielectric properties of this group show frequency independent over a wide range of frequency from 100 Hz up to 1 MHz and temperature independent over a wide range of temperature from room temperature up to 300 oC.